A lipid pathway for ligand binding is necessary for a cannabinoid G protein-coupled receptor - Hurst, Dow P; Grossfield, Alan; Lynch, Diane L; Feller, Scott; Romo, Tod D; Gawrisch, Klaus; Pitman, Michael C; Reggio, Patricia H (The Journal of biological chemistry, 2010)
Recent isothiocyanate covalent labeling studies have suggested that a classical cannabinoid, (-)-7'-isothiocyanato-11-hydroxy-1',1'dimethylheptyl-hexahydrocannabinol (AM841), enters the cannabinoid CB2 receptor via the lipid bilayer (Pei, Y., Mercier, R. W., Anday, J. K., Thakur, G. A., Zvonok, A. M., Hurst, D., Reggio, P. H., Janero, D. R., and Makriyannis, A. (2008) Chem. Biol. 15, 1207-1219). However, the sequence of steps involved in such a lipid pathway entry has not yet been elucidated. Here, we test the hypothesis that the endogenous cannabinoid sn-2-arachidonoylglycerol (2-AG) attains access to the CB2 receptor via the lipid bilayer. To this end, we have employed microsecond time scale all-atom molecular dynamics (MD) simulations of the interaction of 2-AG with CB2 via a palmitoyl-oleoyl-phosphatidylcholine lipid bilayer. Results suggest the following: 1) 2-AG first partitions out of bulk lipid at the transmembrane alpha-helix (TMH) 6/7 interface; 2) 2-AG then enters the CB2 receptor binding pocket by passing between TMH6 and TMH7; 3) the entrance of the 2-AG headgroup into the CB2 binding pocket is sufficient to trigger breaking of the intracellular TMH3/6 ionic lock and the movement of the TMH6 intracellular end away from TMH3; and 4) subsequent to protonation at D3.49/D6.30, further 2-AG entry into the ligand binding pocket results in both a W6.48 toggle switch change and a large influx of water. To our knowledge, this is the first demonstration via unbiased molecular dynamics that a ligand can access the binding pocket of a class A G protein-coupled receptor via the lipid bilayer and the first demonstration via molecular dynamics of G protein-coupled receptor activation triggered by a ligand binding event.